Literature Survey of WATM (International Journal of Engineering and Computer Science, 2017)
ATM (Asynchronous Transfer Mode) has been advocated as an important technology for all types of services and networks. Most people believe that ATM will be the standard for the future B-ISDN (Broadband Integrated Services Digital Network). To ensure the success of ATM, lots of the design issues have been standardized by ATM Forum. Due to the success of ATM on wired networks, wireless ATM (WATM) is a direct t result of the ATM "everywhere" movement. While ATM supports for different traffic characteristics and QOS requirements, WATM networks provide wireless extension to the ATM-based B-ISDN networks by adding mobility support functions. This paper reviews the important aspects of wireless ATM and the handoff related issues. It reviews the basic concepts and benefits of ATM. Then the important features of WATM, service models, protocol model, the key characteristics of WATM and the global activities on WATM are dealt. The paper focuses on the survey of Handoff techniques in WATM and related issues. The Handoff requirements, various strategies and open issues are discussed.